Application of the New IEC International Design Standard for Offshore Wind Turbines to a Reference Site in the Massachusetts Offshore Wind Energy Area. (January 2020) - Roach, Samuel; Park, Se Myung; Gaertner, Evan; Manwell, James; Lackner, Matthew
Abstract: The IEC 61400-3-1 standard for a fixed-bottom offshore wind turbine was applied through simulation of specified Design Load Cases. A metocean data set was assembled based on probability distributions of wind and wave data from a representative site in the Massachusetts Offshore Wind Energy Area. A reference turbine was attached to a monopile substructure created for simulation. FAST simulation outputs from feasible ultimate and fatigue loading design load cases are analyzed and discussed. The requirements of the standard are analyzed for the site-specific certification case. Results show importance of control system failure safety and of mitigation during electrical network loss. Hurricane loading is also discussed.